PENGETAHUAN PROSEDURAL DALAM MENYELESAIKAN MASALAH SISTEM PERSAMAAN LINIER DUA VARIABEL DI SMPN 11 PONTIANAK - Purnamasari, Iga; Halini, Halini; B.S, Dian Ahmad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to describe student's procedural knowledge ability in solving the problem of linear equation system of two variables on the eighth grade students of SMP Negeri 11 Pontianak. The research method used is descriptive and the form of research is survey. The Subject of this research was 33 students of eighth grade of VIII A class of SMP Negeri 11 Pontianak. Based on the result of the test and interview. The results in this research shows that student’s had fairly good procedural knowledge in solving the problem of linear equation system of two variables. The Student’s were able to choose the procedure/method that will be used to solve the problems of linear equation system of two variables based on what they understood, remembered and commonly used. On the aspect of applying the chosen procedure to solve the problem, students were able to apply the procedure of settlement well, only few students were doing mistaken in the calculation.Keywords: Procedural Knowledge, Completing Problem, Solving System of Equations In Two Variable